Chlorophyll fluorescence, stress and survival in populations of Mediterranean grassland species - Figueroa, M. E. (Journal of Vegetation Science, 1997)
Photosynthetic stress in response to a natural episode of frost and seasonal drought was assessed in a ‘dehesa’ grassland of SW Spain with a portable fluorimeter. Chlorophyll fluorescence characteristics of dark-adapted leaves of 11 abundant species of Mediterranean grassland were measured over the course of a growing season from November 1992 to July 1993. Concomitant changes in population size were estimated from censuses of permanent quadrats. There was a general decline in the photochemical efficiency (F v /Fm ) during the growing season and this was particularly evident late in the growing season (spring and early summer) when ambient temperatures were increasing rapidly and rainfall was low; it coincided with the period of most intense mortality for most species. A frost in early March (– 5 °C), when photosynthetically active radiation was relatively high, resulted in a small decrease in F v /Fm that was consistent across many species. The mechanisms of protection in species of Mediterranean grassland appear to be sufficiently effective to avoid damage to PSII for most of the year. For most species there was little evidence of photosystem II damage, as initial fluorescence (F 0 ) usually did not increase. Many of the effects observed were due to a reduction in Fm and thus were consistent with non-photochemical quenching. This could be adaptive in protecting PSII from damage in species that show little evidence of stress. The sharp increase in stress toward the end of the life cycle coincided with the fall in net population size.
Keywords: Drought; Fv/Fm; mortality; Photo-inhibition; photochemical efficiency; Photosystem II